Estado actual del diagnóstico biológico de las infecciones urinarias. - Corral Rosillo, J.; Delgado Martín, J.A.; Gómez Vegas, Ángel; Silmi Moyano, A.; Blázquez Izquierdo, J. (Clínicas Urológicas de la Complutense, 1997)
Sin resumen